Relationship between baseline bicarbonate and 30-day mortality in patients with non-traumatic subarachnoid hemorrhage - Du, Wenyuan; Yang, Jingmian; Lou, Yanfang; You, Jiahua; Wang, Qiang (Frontiers in Neurology, 2024)
Objective: This study aimed to explore the relationship between baseline bicarbonate levels and 30-day mortality in individuals with non-traumatic subarachnoid hemorrhage (SAH).Methods: Patients with non-traumatic SAH were chosen from the Medical Information Mart for Intensive Care (MIMIC)-IV database. The relationship between baseline bicarbonate and 30-day mortality was examined using Cox regression models. Restricted cubic splines were used to test the hypothesis that there was an association between bicarbonate and mortality. With the use of Kaplan-Meier survival curve analysis, we looked deeper into the validity of these correlations. To find subgroups with differences, interaction tests were utilized.This retrospective cohort research consisted of 521 participants in total. Bicarbonate had a negative correlation association with death at 30 days (HR = 0.93, 95%CI: 0.88-0.98, p = 0.004). Next, we divided bicarbonate into quartile groups. In comparison to reference group Q1 (20 mEq/L), group Q3 (23-25 mEq/L) and Q4 (26 mEq/L) had adjusted HR values of 0.47 (95%CI: 0.27-0.82, p = 0.007) and 0.56 (95%CI: 0.31-0.99, p = 0.047). No definite conclusions can be derived from this study since there is no obvious curve link between baseline bicarbonate and 30-day mortality. Patients' 30-day mortality increased statistically significantly (p < 0.001, K-M analysis) in patients with low bicarbonate levels. Bicarbonate and 30-day mortality were continually correlated, according to subgroup analysis. The relationship between bicarbonate and 30-day mortality remained consistent in the stratified analysis, with no observed interactions. Conclusion: 30-day mortality was negatively correlated associated with baseline bicarbonate levels. Patients with non-traumatic SAH are more at risk of mortality if their bicarbonate levels are low.